Qualitative Proteome-Wide Analysis Reveals the Diverse Functions of Lysine Crotonylation in Dendrobium huoshanense - Wu, Jing; Meng, Xiaoxi; Jiang, Weimin; Wang, Zhaojian; Zhang, Jing; Meng, Fei; Yao, Xiaoyan; Ye, Mengjuan; Yao, Liang; Wang, Longhai; Yu, Nianjun; Peng, Daiyin; et al. (Frontiers in Plant Science, 2022)
The lysine crotonylation of histone proteins is a newly identified post-translational modification with diversified cellular functions. However, there are few reports on lysine crotonylation of non-histone proteins in medicinal plant cells. By using high-resolution LC-MS coupled with highly sensitive specific immune-affinity antibody analysis, a whole crotonylation proteome analysis of Dendrobium huoshanense was performed. In total, 1,591 proteins with 4,726 lysine crotonylation sites were identified, among them, eleven conserved motifs were identified. Bioinformatic analyses linked crotonylated proteins to the drought stress response and multiple metabolic pathways, including secondary metabolite biosynthesis, transport and catabolism, energy production and conversion, carbohydrate transport and metabolism, translation, and ribosomal structure and biogenesis. Our study contributes toward understanding the regulatory mechanism of polysaccharide biosynthesis at the crotonylation level even under abiotic stress.